Propriedades estatísticas do ruído Barkhausen em materiais magnéticos artificialmente estruturados - Bohn, Felipe (2009)
Barkhausen noise (BN) corresponds to the voltage pulses induced in a sensing coil wound around a ferromagnetic material submitted to a variable magnetic field. It is related to the irregular motion of the domain walls (DWs) in a disordered magnetic material. Due to its stochastic character, most of the studies aim to explain the BN statistical properties. The statistical functions are, in general, well described by a power-law behavior with cutoff, whose exponents and cutoffs can be compared with the predictions obtained with theoretical models. Interestingly, statistical properties seem to be independent of microscopic and macroscopic details but controlled by a few general properties, as the system dimensionality and range of the relevant interactions governing the DWs dynamics. For bulk materials, there is a well established and consistent interpretation for the BN statistical properties, including the distributions of jump sizes and durations, average size vs. duration and power spectrum, which are related to the exponents t, a, 1=(snz) and J, respectively. In this case, the results clearly indicate that bulk samples present an essentially three-dimensional magnetic behavior and the exponents can be grouped in two distinct universality classes, according the range of interactions governing the DWs dynamics. For ferromagnetic films, the statistical properties are not so well studied due to experimental and theoretical difficulties and most of the experimental results reported so far make use of magneto-optical techniques, which restrict the analysis to the distributions of sizes. In all cases, the reported exponents for films are smaller than that obtained for bulk samples, indicating a possible two-dimensional magnetic behavior. Due to the insufficient amount of experimental data, the structural character and film thickness influence on the exponents was not observed and a complete comprehension of the DWs dynamics in films is still lacking. In this work, we report BN experimental results obtained with the classical inductive method in policrystalline and amorphous ferromagnetic films with thickness in the range 10 - 1000 nm. We investigate the BN statistical properties in order to understand the effects of the interplay between the system dimensionality and the range of the relevant interactions governing the DWs and magnetization dynamics. In particular, we perform an extended statistical analysis which includes the distributions of jump sizes and durations, average size vs. duration curve, power spectrum and the average shape of the Barkhausen jump, reported for the first time for films. The results show evidence of a three to two-dimensional crossover in the DWs dynamics as the film thickness is decreased. Also, the effect of the range of interactions governing the DWs dynamics in this range of thickness is observed, indicating the same two distinct universality classes observed for bulk materials. Through these results, we provide experimental evidence to the validity of different three and two-dimensional heoretical models for DWs dynamics.